The Healing Gaze: Unlocking the Silent Power of Observation in Paediatric Homoeopathic Case Taking. - Parween, Nusrat; Parween, Saniya; Khan, M. A. (Homoeopathic Heritage, 2025)
"A well-taken case is half cured," said Elizabeth Wright. Case taking forms the foundation of effective homeopathic treatment, particularly in pediatrics. It requires collecting detailed, individualized information to build a complete symptom picture. In children, challenges arise as infants cannot speak and older ones may struggle to express themselves. Parental observations, along with the homeopath's sharp interpretive and observational skills, are vital. Rapport-building, effective communication, and attention to nonverbal cues enhance accuracy. This article explores the key principles and challenges of pediatric case taking, emphasizing observation as central to successful homeopathic practice.